Strategic Design of Architecture on the Cloud Service - Daeyu KIM; Choong Hyong LEE; Sangwon LEE, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The architecture of the Cloud Computing can be defined as the components and subcomponents required for the Cloud computing. Usually, the components and subcomponents compromise front-end platforms such as local clients, thin clients, mobile and back-end platforms such as servers, memory. They also include Cloud-based delivery, and networks (like Internet, Intranet, and Intercloud). For 20 years, public Cloud service providers have remained the top three Cloud providers, and characterized by the development of technologies based on software for their own business models and platforms, which have led Information Technology services. As the public Cloud service market develops, its usage spending also increases. And then the increase in spending must be technologically counteracted based on the efficiency of the Cloud. These components are compromised in order to form a Cloud computing architecture. This study aims to derive objective analysis results and implications by proposing the main progress steps so as to analyze the private Cloud service. Its results of our study would make contributions for enterprises to make their policies or decisions before the Cloud Architecture.